Effect of dynamic cyclic loading on screw loosening of retightened versus new abutment screw in both narrow and standard implants (in-vitro study) - Eman Mohammed Nasr Attiah; Attiah Ali AlGendy; Tamer Mohamed Nasr Mostafa (SpringerOpen, 2020)
Abstract Background The purpose of this in-vitro study was to evaluate the effect of dynamic cyclic loading on screw loosening of retightened abutment screw versus new abutment screw in both narrow and standard implants. Methods Separate acrylic resin blocks containing implant assembly (fixture, abutment, abutment screw, metal tube capping the abutment). Samples were divided into two main groups according to the diameter of implant: group 1 (GI 4.5-mm diameter) and group 2 (GII 3-mm diameter). Each group is subdivided into two subgroups according to the suggested option to manage screw loosening either by retightening (GIA, GIIA) or using new screws (GIB, GIIB). One hundred thousand cycles of eccentric dynamic cyclic loading (DCL) were applied before and after retightening or replacing the screw; then, removal torque loss (RTL) ratio was calculated, tabulated, and analyzed by t-student, ANOVA, pair wise Tukey's tests. Results There were differences between GI and GII regarding the incidence of screw loosening process. Removal torque loss ratio was higher in GIB and GIIB where the old abutment screws were replaced by new screws for both standard implants (SIs) and narrow diameter implants (NDIs). There was significant effect of retightening and replacing the abutment screws after exposure to DCL. Conclusions Within the limitations of this in-vitro study, it can be conclude that screw loosening process occurred in both SIs and NDIs but with higher values in NDIs. It is better to retighten the screw of NDIs and SIs than replacing it with a new screw.